The Predictive Factors of CPR Failure After 20 Minutes of Advanced Cardiac Life Support for Non-Traumatic Out-of-Hospital Arrest Cases; a Cross-sectional Study - Huabbangyang, Thongpitak; Sritipsukho, Paskorn (Archives of Academic Emergency Medicine, 2025)
Introduction: In patients with out-of-hospital cardiac arrest (OHCA) who receive advanced cardiac life support (ACLS) for 20 minutes, the decision of whether to continue or terminate resuscitation at the scene is difficult and complicated. This study aimed to develop and validate a simple and reliable clinical scoring system for identifying cardiopulmonary resuscitation (CPR) failure at the scene after 20 minutes of ACLS. Methods: In this cross-sectional study we evaluated the adults with nontraumatic OHCA who received ACLS for 20 minutes. The independent predictors of CPR failure were identified using multivariate regression analysis and trying to develop a clinical decision rule. Receiver operating characteristic (ROC) curve was used for evaluating the performance of the developed model. Results: 455 patients with the mean age of 63.85 ± 19.21 years were included (65.1% male). In most cases of OHCA, the cause of cardiac arrest was respiratory (54.9%). The first cardiac rhythm recorded in 68.1% was asystole. 313 (68.79%) cases were affiliated to the failed CPR group. The independent predictive factors of CPR failure based on multivariate analysis were the first cardiac rhythm recorded (p < 0.001), unwitnessed cardiac arrest (p < 0.001), lack of pupillary response (p < 0.001), advanced airway management at the scene (p < 0.001), and administration of drugs at the scene during CPR, including amiodarone (p = 0.020) and atropine (p = 0.002). The area under the ROC curve of the model was 0.832 (95% confidence interval (CI): 0.793–0.870) with 70.0% sensitivity, 82.4% specificity, 89.8% positive predictive value, 55.5% negative predictive value, 3.97 positive likelihood ratio, and 0.36 negative likelihood ratio. Conclusion: Using data from routine care practices by EMS personnel, we devised a simple clinical scoring system for predicting CPR failure at the scene of OHCA after 20 minutes of complete ACLS.